2010
DOI: 10.1002/ijc.25295
|View full text |Cite
|
Sign up to set email alerts
|

Differential interactions between statins and P‐glycoprotein: Implications for exploiting statins as anticancer agents

Abstract: Statins, prescribed for decades to control cholesterol, have more recently been shown to have promising anticancer activity. Statins induce tumor-selective apoptosis by inhibiting the mevalonate (MVA) pathway. In addition, we have recently demonstrated that lovastatin modulates drug accumulation in a MVA-independent manner in multidrug-resistant (MDR) tumor cells overexpressing the P-glycoprotein (P-gp) multidrug transporter. P-gp-mediated drug efflux can contribute to chemotherapy failure. However, direct sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 54 publications
5
44
0
2
Order By: Relevance
“…In particular, Martirosyan and colleagues (36) recently showed that lovastatin induces apoptosis of ovarian cancer cells and synergizes with doxorubicin, which is used in the treatment of primary and relapsed drug-resistant ovarian cancer. Moreover, lovastatin has been shown to bind directly to the P-glycoprotein and to decrease doxorubicin accumulation in MDR tumor cells (48). Statins such as lovastatin inhibit cholesterol biosynthesis (49), and, therefore, decrease cholesterol intracellular concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Martirosyan and colleagues (36) recently showed that lovastatin induces apoptosis of ovarian cancer cells and synergizes with doxorubicin, which is used in the treatment of primary and relapsed drug-resistant ovarian cancer. Moreover, lovastatin has been shown to bind directly to the P-glycoprotein and to decrease doxorubicin accumulation in MDR tumor cells (48). Statins such as lovastatin inhibit cholesterol biosynthesis (49), and, therefore, decrease cholesterol intracellular concentration.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recent studies showed the contribution of drug transporters as important mechanisms of chemoresistance in ovarian cancer (44,45). For example, as a primary efflux transporter, P-glycoprotein-mediated drug efflux could contribute to chemotherapy failure (45).…”
Section: Discussionmentioning
confidence: 99%
“…For example, as a primary efflux transporter, P-glycoprotein-mediated drug efflux could contribute to chemotherapy failure (45). To our best knowledge, there has been no report about the relationship between iASPP and drug transporters.…”
Section: Discussionmentioning
confidence: 99%
“…One such effect that has recently been addressed is their capacity to interact with P-glycoprotein, a common multidrug transporter. 186,187 Strikingly, both lovastatin and atorvastatin interacted directly with P-glycoprotein in vitro and lovastatin also modulated multidrug resistance in tumor cells. Rosuvastatin and fluvastatin, by contrast, did not interact with P-glycoprotein at biologically relevant concentrations and did not impact tumor cell multidrug resistance.…”
mentioning
confidence: 99%